Senso de coerência, sua relação com cárie dental e seu efeito na qualidade de vida relacionada à saúde bucal - Tomazoni, Fernanda (2017)
Studies have demonstrated that higher sense of coherence (SOC) may lead to better health outcomes. However, there is lack of evidences about the relationship between dental caries and SOC in children and adolescents, mainly on those from low socioeconomic status. Moreover, there are few intervention studies assessing the influence of oral health promotion strategies on oral health outcomes, like oral health related quality of life (OHRQoL) in children. This thesis is composed by two papers. The first one assesses the relationship between SOC and dental cries in socially vulnerable children from Santa Maria, RS; the second article tests the effect of a school-based intervention to enhance SOC and OHRQoL in this children population. Furthermore, it explores the pathways by which the intervention may improve the OHRQoL and SOC. Information about clinical conditions, socioeconomic status, OHRQoL and SOC was obtained from 356 total 8- to 14-year-olds enrolled in 5 schools from Santa Maria. In the second article, the intervention was comprised of 7 sessions over 2 months. OHRQoL and SOC data were collected at baseline, 2 weeks after the intervention, and at three-month follow-up. It was observed that children whose mothers had studied 8 years or less and children with dental plaque presented higher dental caries levels than their counterparts. Higher household income and SOC scores were identified as determinants of lower DMF-T means in children. Furthermore, children who received the SOC-based intervention sessions reported fewer impacts of their oral health on their daily lives compared to those who did not receive the SOC sessions. As would be expected, the intervention group also reported significantly improved SOC at T2 and T3 compared to the control group. This study observed the possible role that SOC could play in improving dental caries status in socially vulnerable children; it also demonstrated that the intervention was effective in improving SOC and OHRQoL in this population.